Práticas pedagógicas e inclusão de estudantes com deficiência intelectual nos anos finais do ensino fundamental - Medeiros, Ricardo Tavares de (2023)
The study seeks to problematize the possibilities and challenges that cross the pedagogical practices mediated by common and special education teachers regarding the schooling of students with intellectual disabilities enrolled in the 7th year of elementary education at a school in the Municipal Network of Vila Velha /ES. It chooses as specific objectives: a) to historicize the special education policy in an inclusive perspective implemented by the Municipal Education Network of Vila Velha/ES, with emphasis on the schooling of students with intellectual disabilities; b) analyze the process of inclusion of these subjects in the researched school; c) problematize issues intrinsic to the pedagogical practices constituted between teachers of common education, special education and students with intellectual disabilities, aiming at the right to learn in regular schools d) create, as an educational product, a guidebook (digital and printed) with reflections on pedagogical practices from an inclusive perspective, with a view to including students with intellectual disabilities in the final years of elementary school. It adopts as a theoretical reference the studies of Vigotski (1991, 2019), the contributions of Meirieu (2002, 2005) and authors in the field of special education. It is based on qualitative assumptions and on a case study, using the following procedures: a) request for data production; b) participant observation; c) semi-structured interviews. It takes place in the context of a class in the 7th year of elementary school, with the enrollment of two students with intellectual disabilities, involving a Portuguese Language teacher, a Mathematics teacher, a Science teacher and a Geography teacher, in addition to the director, coordinator, pedagogue and special education teacher. The data were produced in the second half of 2022 and recorded in a field diary and using a cell phone recorder. As a result, it appears that the municipal network of Vila Velha/ES has been composing special education policies from the perspective of school inclusion since 2005; that the two students participating in the research experience different inclusion processes in the regular classroom; that the conceptualization of intellectual disability, the ways in which planning is carried out at school, the didactic resources and methodologies are used, the articulations between teachers of common education and special education and continuing education in context imply the pedagogical practices and the accessibility to knowledge by students with intellectual disabilities in the researched class.